Novel fluorescence techniques to quantitate renal cell biology - Shroff, Urvi Nikhil (Methods Cell Biol, 2019)
Fluorescence microscopy techniques are powerful tools to study tissue dynamics, cellular function and biology both in vivo and in vitro. These tools allow for functional assessment and quantification along with qualitative analysis, thus providing a comprehensive understanding of various cellular processes under normal physiological and disease conditions. The main focus of this chapter is the recently developed method of serial intravital multiphoton microscopy that has helped shed light on the dynamic alterations of the spatial distribution and fate of single renal cells or cell populations and their migration patterns in the same tissue region over several days in response to various stimuli within the living kidney. This technique is very useful for studying in vivo the molecular and cellular mechanisms of tissue remodeling and repair after injury. In addition, complementary in vitro imaging tools are also described and discussed, like tissue clearing techniques and protein synthesis measurement in tissues in situ that provide an in depth assessment of changes at the cellular level. Thus, these novel fluorescence techniques can be effectively leveraged for different tissue types, experimental conditions as well as disease models to improve our understanding of renal cell biology.